Comparative phylogeography reveals the demographic patterns of neotropical ancient mountain species - Dantas‐Queiroz, Marcos Vinicius; Hurbath, Fernanda; Russo Godoy, Fernanda Maria; Lanna, Flávia Mol; Versieux, Leonardo M.; Palma‐Silva, Clarisse (Molecular ecology, 2023)
Mountains are renowned for their bountiful biodiversity. Explanations on the origin of such abundant life are usually regarded to their orogenic history. However, ancient mountain systems with geological stability also exhibit astounding levels of number of species and endemism, as illustrated by the Brazilian Quartzitic Mountains (BQM) in Eastern South America. Thus, cycles of climatic changes over the last couple million years are usually assumed to play an important role in the origin of mountainous biota. These climatic oscillations potentially isolated and reconnected adjacent populations, a phenomenon known as flickering connectivity, accelerating speciation events due to range fragmentation, dispersion, secondary contact, and hybridization. To evaluate the role of the climatic fluctuations on the diversification of the BQM biota, we estimated the ancient demography of distinct endemic species of animals and plants using hierarchical approximate Bayesian computation analysis and Ecological Niche Modelling. Additionally, we evaluated if climatic oscillations have driven a genetic spatial congruence in the genetic structure of codistributed species from the Espinhaço Range, one of the main BQM areas. Our results show that the majority of plant lineages underwent a synchronous expansion over the Last Glacial Maximum (LGM, c. 21 thousand years ago), although we could not obtain a clear demographic pattern for the animal lineages. We also obtained a signal of a congruent phylogeographic break between lineages endemic to the Espinhaço Range, suggesting how ancient climatic oscillations might have driven the evolutionary history of the Espinhaço's biota.